PERSEPSI DAN PARTISIPASI MASYARAKAT DALAM PELESTARIAN HUTAN RUMAH PELANGI SEBAGAI KAWASAN KONSERVASI (Studi Kasus Hutan Rumah Pelangi, Desa Teluk Bakung, Kecamatan Ambawang, Kabupaten Kubu Raya) - Muhammad Syukur Putra; Sofyan Zainal; M Idham (Universitas Tanjungpura, 2018)
This research aims to determine the level of perception and society participation in forest conservation of Rumah Pelangi as conservation areas. Benefits of this research is to provide feedback for the manager and local authorities to managing the Rumah Pelangi for the sustainability of forest management in its area. The method used is descriptive while the data collection used a structured interview using a questionnaire. The number of respondents in the study were 76 respondents who are local residents and have at least 20 years old with minimum domicile in the are at least 3 years. Research result shows that public perceptions of the forest area in Rumah Pelangi is very low when averaged by the results of the two hamlets percentage did not achieve 50%, and the level of result community participation is low category of all, are under 60%. There is no correlation between perception and society participation in forest preservation of Rumah Pelangi. It is seen of the high number of society perception of Rumah Pelangi, however society participation in managing and protecting the region is very low.Keyword: forest conservation, perception, participation, Rumah Pelangi, society